Evaluating the Effectiveness of Psychological Therapies in Reducing Social Stigma Among Patients with New Stoma - Nga, Nguyen Thi Thuy (South East Asia Nursing Research, 2023)
This review article examines the effectiveness of psychological therapies in reducing social stigma among patients with a new stoma. The synthesis of findings from multiple studies published within the last five years reveals the significant impact of various psychological interventions on reducing stigma and improving patient outcomes. The article outlines the search strategy, inclusion criteria, and analytical methods employed to evaluate the selected studies. The review results demonstrate that psychological therapies, particularly cognitive-behavioral therapy (CBT), substantially mitigate social stigma and enhance the quality of life for stoma patients. However, gaps in research and conflicting evidence on the long-term effectiveness of these interventions are also highlighted. The discussion delves into these findings, offering insights into the practical applications of these therapies and proposing directions for future research. The article concludes by summarizing the implications for clinical practice and offering recommendations for healthcare professionals involved in stoma care.